Electrosynthesis of NH3 from NO with ampere-level current density in a pressurized electrolyzer - Wenqiang Yang; Huan Liu; Xiaoxia Chang; Yunlong Zhang; Yafeng Cai; Yifan Li; Yi Cui; Bingjun Xu; Liang Yu; Xiaoju Cui; Dehui Deng (Nature Communications)
Abstract Electrocatalytic NO reduction reaction (NORR) offers a promising route for sustainable NH3 synthesis along with removal of NO pollutant. However, it remains a great challenge to accomplish both high NH3 production rate and long duration to satisfy industrial application demands. Here, we report an in situ-formed hierarchical porous Cu nanowire array monolithic electrode ensembled in a pressurized electrolyzer to regulate NORR reaction kinetics and thermodynamics, which delivers an industrial-level NH3 partial current density of 1007 mA cm–2 with Faradaic efficiency of 96.1% and remains stable at 1000 mA cm–2 for 100 hours. Integrating the Cu nanowire array monolithic electrode with pressurized electrolyzer boosts the NH3 production rate to 10.5 mmol h–1 cm–2, which is over tenfold that using commercial Cu foam at 1 atm. The NORR performance can be attributed to the promoted NO mass transfer to the enriched Cu surface, which could increase the NO coverage on Cu and then destabilize adsorbed NO and weaken hydrogen adsorption, thereby facilitating NO hydrogenation to NH3 while suppressing the competing hydrogen evolution.